2014
DOI: 10.1371/journal.pone.0107745
|View full text |Cite
|
Sign up to set email alerts
|

Separation Anxiety, Attachment and Inter-Personal Representations: Disentangling the Role of Oxytocin in the Perinatal Period

Abstract: In this paper, we aimed to assess cross-sectionally and longitudinally associations between disturbances in maternal early attachment experiences, symptoms of separation anxiety and depression and oxytocin plasma levels. We examined a mediational model that tested the hypothesis that anxious attachment style arising from the mothers’ early bonding experiences with her own parents was associated with high levels of separation anxiety which, via its impact on depression, was associated with reduced levels of oxy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
60
1
8

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 86 publications
(76 citation statements)
references
References 57 publications
(69 reference statements)
2
60
1
8
Order By: Relevance
“…The relationship between OT and maternal depressive symptoms during the perinatal period has received increasing attention (Eapen et al 2014), and the conventional role of OT as a hormone that is primarily involved in childbirth and lactation has undergone a significant expansion (McQuaid et al 2014). In this review, six studies were identified that addressed the association between OT level and maternal depression during gestation or postpartum periods.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The relationship between OT and maternal depressive symptoms during the perinatal period has received increasing attention (Eapen et al 2014), and the conventional role of OT as a hormone that is primarily involved in childbirth and lactation has undergone a significant expansion (McQuaid et al 2014). In this review, six studies were identified that addressed the association between OT level and maternal depression during gestation or postpartum periods.…”
Section: Discussionmentioning
confidence: 99%
“…OT has also recently been implicated in the pathophysiology of several neuropsychiatric disorders. Furthermore, several studies provided evidence for a relationship between OT and behavioral adaptation to motherhood (Skrundz et al 2011), as well as bonding and the parent-infant relationship (Eapen et al 2014). In addition to OT's therapeutic potential for a wide variety of other psychiatric conditions, increasing attention is now directed to PPD as another possible target for its therapeutic benefit (Kim et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…While the human research literature is at a more preliminary Available online at www.sciencedirect.com ScienceDirect Comprehensive Psychiatry 76 (2017) 56 -68 www.elsevier.com/locate/comppsych stage, a similar picture is emerging. Mothers with rising plasma oxytocin levels across pregnancy have reported more positive maternal-fetal attachment [9], and higher maternal plasma oxytocin levels in the early postpartum period have been shown to be associated with more positive maternal representations and stronger feelings of bonding to the infant [10,11]. Studies have also shown oxytocin levels during pregnancy and the early postpartum period to be positively associated with a range of sensitive and responsive postnatal caregiving behaviors including affectionate touch, vocalizations and synchrony of mother-infant gaze and affect [4,12].…”
Section: Introductionmentioning
confidence: 99%
“…While self-report adult attachment scales do not provide objective information or information as to whether an individual has 'resolved' previous trauma, including abuse and loss experiences, evidence suggests overlap between some aspects of self-report attachment questionnaires and interviews assessing attachment state-of-mind constructs [17,18] and links between attachment insecurity and compromised parenting [3]. Eapen et al [10] recently showed that an anxious attachment style was associated with lower maternal peripheral oxytocin levels and poorer self-reported bonding with the infant at three months postpartum. Taken together, the studies of Strathearn et al [14] and Eapen et al [10] indicate a positive association between adult attachment security and maternal oxytocin (baseline levels and response following mother-infant interaction), and provide evidence to suggest that these variables may explain more variance in parenting outcomes than either one alone.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation